FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN KERJA KARYAWAN BAGIAN PEMETIK TEH DI PT PERKEBUNAN TAMBI, UNIT PERKEBUNAN TAMBI, KABUPATEN WONOSOBO - Komen, Komen; Nadapdap, Hendrik Johannes (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 13 No 3 (2019): Vol. 13, No. 3, 2019, 2019)
Employee’s work satisfaction is used to describe the employee’s feeling towards their work. This research was aimed to describe the employee’s work satisfaction and analyze the effect of some factors, such as work motivation, organization culture, leadership style, work facility and work environment toward the work satisfaction of the employees in Tambi Tea Plantation Factory, Tambi Plantation Unit, Wonosobo Regency. The method used for this research was survey. The sampling technique used was random sampling technique, which consisted of 57 respondents. The research started from January to February 2019. The data were then analyzed through descriptive analysis and multiple linear regression. The research result showed that the employees felt satisfied when working as tea leaf pickers for this work gave them challenges, they got the proper salary, conducive working place, they showed some respect to each other, and also got the job that fitted desire. Work motivation variable (X 1 ), organization culture (X 2 ), and work environment (X 5 ) had significant effect toward the employee’s work satisfaction (Y). Whereas leadership style (X 3 ) and work facility (X 4 ) did not have significant effect toward the employee’s work satisfaction (Y).